ANALYSIS OF THE PSYCHOLOGICAL STATE OF FOOTBALL PLAYERS ENGAGED IN THE STUDY TRAINING GROUP DURING THE TRAINING PROCESS (Scientific journal of the Fergana State University, 2024)
In this article, the author highlights the scientific and methodological aspects of the psychological training of football players in the the Ch.D.Spielberger reactive anxiety scale on an experimental basis.